Comparison Resilience of UNAI Dormitorium Male and Female Students During Pandemic Covid 19, March to May 2020 - Elon, Yunus; Walukour, Yane Restuwaty (8ISC Proceedings: Covid-19, 2022)
The Covid-19 pandemic is the most serious and potentially transformative event of our lifetime. We are only at the earliest stage of major disruptions to the lives of individuals and families, communities, the national economy, supply chains, critical infrastructure, and agriculture worldwide. Concerns about Covid-19 have brought rapid changes, which can bring stress, anxiety, and fear. Our foundation may feel unstable, our grasp and sense of control may feel tenuous. Losing any relatives and loved ones, dismissal from jobs, a disaster such as an earthquake, fire, along with terrorist attack influence people deeply. Despite being exposed to such severe conditions, people recover themselves even if they cannot completely forget these risky situations. Psychological resilience is perceived as an adaptation process to normal life pace (Tusale & Dyer, 2004). This study aims to measure the resilience of 280 Universitas Advent Indonesia (UNAI) students, which is composed of 185 female students (66%) and 95 male students (34%). A quantitative survey was conducted to compare resilience between Female and Male UNAI Students from March to May 2020, using the Connor-Davidson Resilience Questionnaire with (0.94% Reliability). The result describes that UNAI Female students have a grand mean resilience of 3,6339, and Male students have a lower grand mean resilience of 3,5503. It can be concluded that UNAI female students’ resilience is higher than the male students. Keywords : Covid-19, pandemic, resilience, male, female